Biofertilizer Application to Enhance The Oil Palm Growth and Productivity - Hidayat, Fandi; Yudhistira, Yudha; Desika Putri Pane, Rizki; Sapalina, Fadilla; Listia, Eka; Amalia, Rizki; Muhayat, Muhayat; Winarna, Winarna (Jurnal Penelitian Kelapa Sawit, 2023)
The conventional soil management practices employed in oil palm plantations often overlook the critical aspect of soil biology, leading to potential detrimental effects on soil health and fertility, primarily driven by the excessive utilization of inorganic fertilizers. However, there is growing evidence that biofertilizers, comprising beneficial bacterial consortia, hold significant promise as an alternative approach for sustainable agriculture while mitigating environmental impacts. Extensive research has been conducted to explore the application of biofertilizers and investigate their impact on the growth and yield of oil palm. In a study conducted on a demo plot of oil palms planted in 2008 in South Sumatra since 2019, a randomized complete block design with five treatments was implemented. The application of biofertilizers yielded notable outcomes, including a substantial increase in the bacterial population, surpassing the threshold of 108 cfu.g-1. This upsurge in bacterial populations signifies a positive shift towards enhanced soil microbial activity and functioning. Furthermore, the application of biofertilizers demonstrated significant improvements in crucial growth parameters. Leaf area exhibited an increase ranging from 8.5% to 17.2%, while dry frond biomass showed a remarkable boost ranging from 8.6% to 14.9%, in comparison to the usage of 100% inorganic fertilizers. Moreover, the combination of inorganic fertilizers with biofertilizers (S75B1, S75B2, S50B1, and S50B2) exhibited enhanced fertilizer efficiency and ultimately resulted in higher oil palm yields compared to the usage of 100% inorganic fertilizers. This valuable finding underscores the potential of integrating biofertilizers into conventional fertilization practices to achieve optimal agricultural productivity while minimizing environmental impact.